MODEL CORPORATE SOCIAL RESPONSIBILITY DALAM PROGRAM PEMBERDAYAAN PETANI HORTIKULTURA - Etty Soesilowati; Dyah Rini Indriyanti; Widiyanto Widiyanto (Muhammadiyah University Press, 2011)
This research aimed to analyze the model of empowering dry land farmers in Central Java, the actors involved, the constraints faced, the impact and level of effectiveness. The study used two approaches: qualitative and quantitative approaches. In the qualitative approach, data were analyzed by using an interactive model. While the quantitative approach carried out by using the cost and benefit analysis. In the qualitative approach, data were analyzed by using an interactive model. While the quantitative approach conducted by using the cost and benefit analysis. The results showed that CSR was done through the assistance of technical consultants by applying concept